3D numerical investigation of water flow on unsymmetrical chute spillway - Saidin M.S.I.; Aziz M.S.A.; Zainol M.R.R.M.A.; Ishaik M.H.H.; Luo P.; Malek M.A. (American Institute of Physics Inc., 2023)
Smooth spillway is a classic design that been use for spilling the massive water flow down from the dam's reservoir. The scale-down model of the smooth spillway with the unsymmetrical shape had been investigating numerically. Due to the unsymmetrical shape, the velocity and the water surface characteristics of at the smooth chute area had been studying by using 3D numerical simulation applixxcation. Realizable ?-e (RKE) turbulence model and volume of fluid (VOF) method had been used to simulate the water flow from the upstream to the downstream of the smooth spillway. The results provide an excellent prediction of the hydraulic characteristics on unsymmetrical smooth chute region. The spanwise of water surface contours and the streamwise water volume fraction profiles were successfully predicted the uneven water surface and the standing waves development at the midplane of spillway. While the streamwise velocity distribution profile has shown slightly different profile pattern at each side of the plane. In the future work will be conducted to validate and verify the simulation results with the experiment results. 2020 Author(s).